The Role of Technology in Enhancing Student Engagement and Performance: A Case Study in Eswatini Secondary School Educational Settings - Olayinka, Adesola Afolayan; Fashion Phiri (IJRDO- Journal of Educational Research, 2024)
The paper uses the case study approach to estimate the impact brought by technology on students’ engagement and academic performance. The quantitative data target was from 296 students and 48 teachers, including 25 Administrative/Support Staff and 10 observation Checklists across all secondary schools in Manzini Region of the kingdom of Eswatini. The research has employed correlation and regression methods to bring out the impacts that utilization of technological development and support bring on student engagement and performance. These findings depict the use of technology within a curriculum as greatly enhancing learners’ engagement, hence academic performance. Recommendations at the end of the paper note that educators and policy makers should make use of technology in ways that enhance learning experiences.